2022
DOI: 10.1111/1365-2745.13926
|View full text |Cite
|
Sign up to set email alerts
|

Citizen science across two centuries reveals phenological change among plant species and functional groups in the Northeastern US

Abstract: 1. Understanding the breadth and complexity of changes in phenology is limited by the availability of long-term historical data sets with broad geographic range.2. We compare a recently discovered historical data set of plant phenology observations collected across the state of New York (1826-1872) to contemporary volunteer-contributed observations (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) to evaluate changes in plant phenology between time periods. These multi-site, multi-taxa phenology data matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…While generally lacking the in‐depth site‐specific detail found in Grinnell's, Bertelsen's, and Thoreau's datasets, these data can still be used to explore broad patterns and test specific hypotheses (Fuccillo Battle et al . 2022).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…While generally lacking the in‐depth site‐specific detail found in Grinnell's, Bertelsen's, and Thoreau's datasets, these data can still be used to explore broad patterns and test specific hypotheses (Fuccillo Battle et al . 2022).…”
Section: Figurementioning
confidence: 99%
“…In other cases, researchers may find unexpectedly detailed regional-scale datasets. For example, Fuccillo Battle et al (2022) recently began analyzing data from one of the oldest citizenscience networks in North America, a network started by the New York State Regents in 1826 to monitor weather and phenology. After comparing the historical data to modern citizenscience observations to assess changes in plant phenology across the state of New York, the research team found significant variation in phenological changes across functional groups (e.g., insect-versus wind-pollinated taxa) and locations (e.g., urban versus rural), with implications for altered ecological interactions.…”
Section: Richardmentioning
confidence: 99%
See 1 more Smart Citation
“…Such community-sourced data have significantly contributed to the accumulation of ecosystem information. These datasets have been instrumental in assessing the impacts of climate change and urbanization on phenology (Fuccillo Battle et al, 2022;Klinger et al, 2023), detecting distribution changes including invasive alien species (Larson et al, 2020;Roy et al, 2023;Wallace & Bargeron, 2014), exploring large-scale geographic variations in traits (Atsumi & Koizumi, 2017;Leighton et al, 2016), and estimating species distributions (Chandler et al, 2017;Feldman et al, 2021;Johnston et al, 2018;Steen et al, 2019). Moreover, the utilization of machine learning to describe population trends based on community-sourced data (Fink et al, 2023) offers opportunities for conducting time-series analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic climate change has significantly altered the timing of life history events (i.e., phenology) of plants worldwide ( 1 , 2 ). For instance, plants in New York state USA have been shown to flower 10.5 d earlier on average in contemporary years than in the early to mid-19th century in response to warming spring temperatures ( 3 ). Such shifts in flowering time affect the reproduction and survival of plant species as well as those of other species that interact with them ( 4 7 ).…”
mentioning
confidence: 99%